Career stage dependent effects of law firm governance: A multilevel study of professional-client misconduct. (September 2019) - Lander, Michel W; van Oosterhout, J (Hans); Heugens, Pursey; Pruijssers, Jorien L
Are governance practices employed by professional service firms equally effective in preventing professional-client misconduct for professionals at different stages of their career? Drawing upon professional-agency theory and the literature documenting professional career patterns, we develop a multilevel theoretical model to answer this question. We test our model in the empirical context of the Dutch legal profession, using firm-level survey data on 142 law firms and individual-level archival data from the 2994 lawyers working for these firms to explain 97 formally adjudicated complaints of professional-client misconduct committed by individual lawyers registered with the Amsterdam Bar Association. We find that the 'orthodox' distinction between informal behavioral and formal outcome-based governance practices is too course-grained to receive empirical support, and that firm-level governance practices only reduce professional-client misconduct when they are specifically targeted at the career stage of the lawyers employed. Our findings not only allow us to develop a finer-grained version of Sharma's professional-agency model, but may also be practically useful in developing firm-level governance practices targeted at different strata of professionals.